2017
DOI: 10.1371/journal.pntd.0005525
|View full text |Cite
|
Sign up to set email alerts
|

Catalase protects Aedes aegypti from oxidative stress and increases midgut infection prevalence of Dengue but not Zika

Abstract: BackgroundDigestion of blood in the midgut of Aedes aegypti results in the release of pro-oxidant molecules that can be toxic to the mosquito. We hypothesized that after a blood meal, the antioxidant capacity of the midgut is increased to protect cells against oxidative stress. Concomitantly, pathogens present in the blood ingested by mosquitoes, such as the arboviruses Dengue and Zika, also have to overcome the same oxidative challenge, and the antioxidant program induced by the insect is likely to influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 57 publications
0
72
1
1
Order By: Relevance
“…In Ixodes ricinus tick, it has been reported that there are more sulfotransferase transcripts in tick midgut after blood feeding than before [67]. The same pattern was observed with catalase transcripts in Aedes aegypti [56]. In Dermacentor variabilis tick, blood intake promotes the up-regulation of glutathione-S transferase (GST) transcription in midgut and ovary [24].…”
Section: Hematophagousmentioning
confidence: 90%
“…In Ixodes ricinus tick, it has been reported that there are more sulfotransferase transcripts in tick midgut after blood feeding than before [67]. The same pattern was observed with catalase transcripts in Aedes aegypti [56]. In Dermacentor variabilis tick, blood intake promotes the up-regulation of glutathione-S transferase (GST) transcription in midgut and ovary [24].…”
Section: Hematophagousmentioning
confidence: 90%
“…Nonetheless, protecting measures such as releasing catalase might facilitate infection of the epithelial cells in the midgut by viruses like DENV [91, 92]. Nevertheless, more studies will be necessary to establish the overall role of these events in arboviruses.…”
Section: Additional Factors Related To Infectionin Mosquitoesmentioning
confidence: 99%
“…Recent studies revealed that intraperitoneal injection of hydrogen-rich saline has surprising anti-inflammation, anti-oxidant, anti-apoptosis effects and protected organism against polymicrobial sepsis injury, acute peritonitis injury both by reducing oxidative stress and via decreasing mass proinflammatory responses. It is also well known that the majority of viral -induced tissue damage and discomfort are mainly caused by an inflammatory cytokine storm and oxidative stress rather than by virus itself [3][4][5]. Studies have shown that suppressing the cytokine storm and reducing oxidative stress can significantly alleviate the symptoms of influenza and other severe viral infections diseases [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, molecular hydrogen was considered a surprising agent, which can significantly reduce oxidative stress by selectively reducing hydroxyl radical Hutaohong2010@163.com (•OH) and Peroxynitrite (ONOO-) [1,[8][9][10]. It has recently been revealed that hydrogen can both down-regulate expression of oxidative-related genes and pro-inflammatory cytokine genes directly and indirectly [2][3][4][5]11,12]. Oxidative stress and systemic inflammatory response syndrome have been confirmed to play critical roles in tissue and organ damages after polymicrobial sepsis injury, acute peritonitis injury, and peritonitis, which can develop into lethal sepsis with inappropriate treatment [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation